Merkel Cell Polyomavirus-Specific CD8+ and CD4+ T-cell Responses Identified in Merkel Cell Carcinomas and Blood - Iyer, Jayasri G.; Afanasiev, Olga K.; McClurkan, Christopher; Paulson, Kelly; Nagase, Kotaro; Jing, Lichen; Marshak, Joshua O.; Dong, Lichun; Carter, Joseph; Lai, Ivy; Farrar, Erik; Byrd, David; et al. (Clinical cancer research, 2011)
Purpose: Merkel cell polyomavirus (MCPyV) is prevalent in the general population, integrates into most Merkel cell carcinomas (MCC), and encodes oncoproteins required for MCC tumor growth. We sought to characterize T-cell responses directed against viral proteins that drive this cancer as a step toward immunotherapy. Experimental Design: Intracellular cytokine cytometry, IFN-γ enzyme-linked immunospot (ELISPOT) assay, and a novel HLA-A*2402–restricted MCPyV tetramer were used to identify and characterize T-cell responses against MCPyV oncoproteins in tumors and blood of MCC patients and control subjects. Results: We isolated virus-reactive CD8 or CD4 T cells from MCPyV-positive MCC tumors (2 of 6) but not from virus-negative tumors (0 of 4). MCPyV-specific T-cell responses were also detected in the blood of MCC patients (14 of 27) and control subjects (5 of 13). These T cells recognized a broad range of peptides derived from capsid proteins (2 epitopes) and oncoproteins (24 epitopes). HLA-A*2402–restricted MCPyV oncoprotein processing and presentation by mammalian cells led to CD8-mediated cytotoxicity. Virus-specific CD8 T cells were markedly enriched among tumor infiltrating lymphocytes as compared with blood, implying intact T-cell trafficking into the tumor. Although tetramer-positive CD8 T cells were detected in the blood of 2 of 5 HLA-matched MCC patients, these cells failed to produce IFN-γ when challenged ex vivo with peptide. Conclusions: Our findings suggest that MCC tumors often develop despite the presence of T cells specific for MCPyV T-Ag oncoproteins. The identified epitopes may be candidates for peptide-specific vaccines and tumor- or virus-specific adoptive immunotherapies to overcome immune evasion mechanisms in MCC patients. Clin Cancer Res; 17(21); 6671–80. ©2011 AACR.